Contributions of selected fundamental factors to wheelchair basketball performance - Wang, Y. T.; Chen, S.; Limroongreungrat, W.; Change, L. S. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The purpose of this study was to determine the contributions of selected fundamental factors, such as arm length, sitting height, simple vision reaction time (SVRT), choice vision reaction time (CVRT), muscle strength, and range of motion (ROM) at the shoulder, elbow, and wrist joints to wheelchair basketball (WCB) performance as measured by season statistics and coaches' evaluation.